Acute bilateral sensorineural hearing loss: an unexpected and early presentation of acute stroke - Hoo, Fan Kee; Boo, Yang Liang; Mohd Sazlly Lim, Sazlyna; Wan Sulaiman, Wan Aliaa; Ching, Siew Mooi; Ramachandran, Vasudeven (Pakistan Medical Association Rawalpindi Islamabad Branch, 2015)
We report a case of acute ischemic stroke presented as acute bilateral sensorineural hearing loss. 47 year-old man presented with bilateral hearing loss for one day. Pure tone audiometry revealed moderate bilateral sensorineural hearing loss. Magnetic resonance imaging and magnetic resonance angiogram (MRA) revealed left vertebral artery thrombosis with partial thrombosis of the basilar artery.